A negative elongation factor E inhibits white spot syndrome virus replication by suppressing promoter activity of the viral immediate early genes in red claw crayfish Cherax quadricarinatus. (June 2020) - Gao, Yan; Liu, Ling-ke; Wang, Ke-jian; Liu, Hai-peng
Abstract: Invertebrates rely solely on the innate immune system to protect against virus infection, while the viral infection must rely on the transcriptional system of the host cell to achieve the expression of viral genes, which is naturally regulated by the host's transcriptional system. However, the mechanism of the host against viral transcription in host cells is still poorly understood in crustaceans. Previously, we found that the partial transcript sequence of a negative elongation factor E (named as CqNELF-E ) was up-regulated in a differentially expressed transcriptome library of the haematopietic tissue (Hpt) cells from red claw crayfish Cherax quadricarinatus upon white spot syndrome virus (WSSV) infection, suggesting a possible role of CqNELF-E in WSSV-host interaction. In the present study, we revealed the function of CqNELF-E. The full-length cDNA sequence of CqNELF-E was identified with 1726 bp from red claw crayfish, which contained an open reading frame of 816 bp, encoding 271 amino acids. Amino acid sequencing analysis revealed that the CqNELF-E had a conserved RNA recognition motif (RRM) and a leucine zipper motif (LZM). Tissue distribution analysis showed that CqNELF-E was widely expressed in various tissues with the highest expression in muscle, relatively abundant in Hpt and the lowest presence in heart. Interestingly, the gene expression of CqNELF-E was significantly up-regulated at both 6 and 12 hpi after WSSV infection in Hpt cell cultures in red claw crayfish. In addition, the expression of both the viral immediately early gene (IE) 1 (IE1) and a late gene envelope protein VP28 were significantly increased after gene silencing of CqNELF-E in Hpt cells, indicating the potential suppression role of CqNELF-E against the viral infection. Further study revealed that the CqNELF-E had an inhibitory effect on the promoter activity of WSSV IE genes WSV051, WSV069 (IE1) and WSV083 by a dual luciferase reporter gene assay. Taken together, these results suggest that CqNELF-E plays an antiviral role, probably via inhibition on the viral transcription activity in WSSV infection in a crustacean. Highlights: CqNELF-E is involved in antiviral immunity. CqNELF-E may inhibit the replication of WSSV. CqNELF-E functions in suppressing the promoter activity of WSSV IE genes. Cq NELF-E function may provide new strategy against white spot disease.